Utility of patient-derived xenografts to evaluate drug sensitivity and select optimal treatments for individual non-small-cell lung cancer patients - Xiaoqing Wang; Ju Zhu; Lingling Li; Qilin Zhao; Yutang Huang; Chunjie Wen; Dan Chen; Lanxiang Wu (Molecular Medicine)
Abstract Background Patient-derived xenograft (PDX) is currently considered a preferred preclinical model to evaluate drug sensitivity, explore drug resistance mechanisms, and select individualized treatment regimens. Methods Histopathological examination, immunohistochemistry and whole-exome sequencing confirmed similarity between our PDX tumors and primary tumors in terms of morphology and genetic characteristics. The drug reactivity of the PDX tumor was validated in vivo. The mechanisms of acquired resistance to Osimertinib PDX tumors were investigated by WES and WB. Results We successfully established 13 NSCLC-PDXs derived from 62 patients, including eight adenocarcinomas, four squamous-cell carcinoma, and one large-cell neuroendocrine carcinoma. Histological subtype and clinical stage were significant factors affecting the successful PDXs establishment. The treatment responses to conventional chemotherapy in PDXs were entirely consistent with that of their corresponding patients. According to the genetic status of tumors, more appropriate targeted agents were selected in PDXs for their corresponding patients as alternative treatment options. In addition, a PDX model with acquired resistance to osimertinib was induced, and the overactivation of RAS mitogen-activated protein kinase (MAPK)-extracellular signal-regulated kinase (ERK) signaling pathway caused by the dual-specificity phosphatase 6 (DUSP6) M62I mutation was found to play a key role in the development of osimertinib resistance. Trametinib, a specific inhibitor of the MAPK-ERK pathway significantly slowed down the tumor growth in osimertinib-resistant PDX models, providing an alternative treatment in patients after osimertinib failure.